CHALLENGES IN THE IMPLEMENTATION OF INSTRUCTIONAL STRATEGY MODEL BASED ON THE BRAIN NATURAL LEARNING SYSTEMS FOR INCLUSIVE CLASSROOM: Received: 19th September 2021; Revised: 20th December 2021, 3rd January 2022, 9th January 2022; Accepted: 10th January 2022 - Rasmitadila, .; Widyasari, .; Prasetyo, Teguh; Putri, Ayu Anggraini (PUPIL: International Journal of Teaching, Education and Learning, 2022)
One of the problems teachers often face in inclusive classrooms is the difficulty of designing effective and flexible instruction that can meet the needs of all students. This study explores general teacher (GT) opinions on the challenges in implementing instructional strategies based on the natural brain learning systems for inclusive classrooms in elementary schools. Data were collected through classroom observations and semi-str One of the problems teachers often face in inclusive classrooms is the difficulty of designing effective and flexible instruction that can meet the needs of all students. This study explores general teacher (GT) opinions on the challenges in implementing instructional strategies based on the natural brain learning systems for inclusive classrooms in elementary schools. Data were collected through classroom observations and semi-structured interviews with seven GTs who have implemented instructional strategies based on the natural brain learning system in an inclusive classroom. Data were analyzed using thematic analysis. The research has four main themes: modification of teaching materials, modification of instructional methods, modification of instructional media, and time. The challenge in implementing instructional strategies based on the natural learning system of the brain lies in the readiness of GTs in facing all changes in the instructional process that GTs has implemented. This challenge will expect to be the experience of GTs in designing more effective learning that must fully support all parties to provide meaningful learning for all students. uctured interviews with seven GTs who have implemented instructional strategies based on the natural brain learning system in an inclusive classroom. Data were analyzed using thematic analysis. The research has four main themes: modification of teaching materials, modification of instructional methods, modification of instructional media, and time. The challenge in implementing instructional strategies based on the natural learning system of the brain lies in the readiness of GTs in facing all changes in the instructional process that GTs has implemented. This challenge will expect to be the experience of GTs in designing more effective learning that must fully support all parties to provide meaningful learning for all students.